Casein phosphopeptide-amorphous calcium phosphate varnish versus dentin desensitizer in the treatment of non-carious dentin hypersensitivity - Bhat, Pallavi; Shetty, Apoorva; Thimmaiah, Charisma; Dsouza, Anita Precilla; D'souza, Sonia Preshma; Bhat, Poornima (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Dentin hypersensitivity (DH) is one of the most common conditions clinicians encounter in clinical practice. New techniques are continuously being set forth to treat this condition. In recent times, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) has garnered attention owing to its ability to improve remineralization and prevent enamel demineralization. Consequently, it has been indicated as an advanced treatment for DH. Purpose: This clinical trial aims to assess the efficacy of a CPP-ACP varnish in the management of non-carious cervical hypersensitivity and compare it with that of a dentin desensitizer. Methods: Patients between the ages of 20 and 65 years who reported to our institute with complaints of DH were selected for this study. Forty teeth were chosen for this study and randomly assigned to two groups. The test group was treated with a CPP-ACP varnish (MI Varnish®, GC Corporation, Japan), while the control group was treated with a dentin desensitizer (Gluma®, Heraeus-Kulzer, Germany). Dentin hypersensitivity assessments were conducted during pre-treatment, immediately following treatment, and 2 and 4 weeks after treatment. Statistical analysis was performed after data collection. Results: An intragroup comparison showed both the CPP-ACP varnish and the dentin desensitizer achieved a maximum decrease in sensitivity in the time interval from baseline to post-op, and these desensitizing effects were sustained through the second and fourth week following treatment. An intergroup comparison revealed no statistically significant difference in sensitivity between the two groups at different time intervals. Conclusion: It could be concluded that CPP-ACP varnish and dentin desensitizer possess similar efficacy in the treatment of DH.